"Because it is my name!": Miller, Proctor, and Parrhesia in The Crucible. (2nd March 2018) - Jeihouni, Mojtaba; Hooti, Noorbakhsh
Abstract : This article offers a Foucauldian reading of Arthur Miller's The Crucible . Employing Foucault's concept of parrhesia, we argue that John Proctor holds truth‐telling as a moral virtue and accordingly his behavior qualifies as parrhesiastic based on the five elements Foucault outlines for parrhesia : frankness, truth, danger, criticism, and duty. First we shall provide a thorough account of the concept in Foucault's work. Second, and on the basis of that account, we shall explore the relations of power in Miller's play, arguing that Proctor deconstructs the self‐celebrating dogmatism of his Puritan context with a razor‐sharp honesty. We shall conclude that Proctor meets his death because of his parrhesiastic courage.